2020
DOI: 10.4103/jrms.jrms_116_19
|View full text |Cite
|
Sign up to set email alerts
|

The sequential assay of interleukin-10 and 13 serum levels in relation to radiographic changes during pulmonary tuberculosis treatment

Abstract: Background: We evaluated the sequential changes of interleukin (IL)-10 and IL-13 serum levels with tuberculosis (TB)-related radiographic changes during pulmonary TB (PTB) treatment. Materials and Methods: In this cross-sectional study during two consecutive years, forty cases with PTB were recorded, and finally, 24 cases were completed the study. Serum levels of IL-10 and IL-13 were measured on admission time, and 6 months later. Furthermore, chest radiography was perf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…Another study [19] also observed increased IL-6, alongside CRP and TNF-α, in pTB patients, indicating diverse inflammatory pathways in pTB. Namaei M et al [20] showed a significant upregulation of serum IL-10 in patients with normal spirometry and its downregulation with obstructive spirometry during tuberculosis treatment. IL-10, an anti-inflammatory cytokine, contributes to less inflammation-related lung damage in pulmonary infections.…”
Section: Discussionmentioning
confidence: 98%
“…Another study [19] also observed increased IL-6, alongside CRP and TNF-α, in pTB patients, indicating diverse inflammatory pathways in pTB. Namaei M et al [20] showed a significant upregulation of serum IL-10 in patients with normal spirometry and its downregulation with obstructive spirometry during tuberculosis treatment. IL-10, an anti-inflammatory cytokine, contributes to less inflammation-related lung damage in pulmonary infections.…”
Section: Discussionmentioning
confidence: 98%
“…Diagnosis and treatment of LTBI is recommended for patients undergoing transplantation. [ 13 14 15 ] Recipients are at increased risk of developing TB disease. Studies show that 1%–15% of patients undergoing organ transplantation develop the disease.…”
Section: Discussionmentioning
confidence: 99%